Identification of Legionella by MALDI Biotyper through three preparation methods and an in-house library comparing phylogenetic and hierarchical cluster results - Luna Girolamini; Paolo Caiazza; Federica Marino; Maria Rosaria Pascale; Laura Caligaris; Simona Spiteri; Carlo Derelitto; Maria Luisa Simone; Antonella Grottola; Sandra Cristino (Scientific Reports)
Abstract The identification and typing of bacteria are very expensive and time-consuming due to their growth times, and the expertise needed. MALDI-TOF MS represents a fast technique, reproducible with molecular approaches. This technique is still poorly applied in Legionella surveillance with estimation occurring only at the genus level. The aim of this study was to compare three sample preparation methods: direct smear (DS), extended direct smear (EDS), and full extraction (E), using MALDI Biotyper, developing an in-house library. Moreover, Hierarchical cluster analysis (HCA) was compared to mip and rpoB gene sequencing. The dataset was composed of 104 isolates belonging to six Legionella species. The isolates were identified with a sensitivity of 97.11% for DS, 98.08% for EDS, and 95.19% for E. The error rates were 2.88% for DS, 1.92% for EDS, and 4.90% for E, with no significant differences among them. The HCA confirmed the relationship among the isolates reported in the phylogenetic trees. An improvement in sensitivity was obtained using an in-house library. The results suggest the use of a fast and inexpensive DS method, combined with instrument and in-house library for routine Legionella surveillance. HCA analysis could be useful for screening isolates, before undertaking expensive and time-laborious molecular techniques.